How Title VII Erodes the Mission of the Religious University - Zigarelli, Michael A. (International journal of value-based management, 1998)
For decades, courts have held that Title VII of the Civil Rights Act of 1964 does not permit religious universities to consider a job applicant's religious beliefs when staffing most faculty and administrative positions. This article briefly reviews the law in this area and then applies the vast body of research on ’organizational culture' to argue that this judicial interpretation will, in the long-run, undermine the religious university's ability to perpetuate its mission.